Human capital and economic growth: empirical evidence from Malaysia - Mohammad Rusli, Norhanani Aflizan; Hamid, Zarinah (2014)
The objective of this paper is to estimate the long and short run relationship between human capital and economic growth in Malaysia. The study applies rigorous empirical testing to test the validity of the model. Data derived from different sources undergo unit root tests to ensure stationarity at level or first difference. It also utilizes cointegration test, error correction model (ECM), short-run Granger causality, variance decomposition and impulse response function to analyze the impact of human capital on economic growth in the long and short run. The results confirmed that education, government expenditure and economic growth have long run relationships. The results of successful human capital development will not be seen in an instant, but rather over a period of time. In line with Malaysia’s aspiration to become a high income nation in 2020, efforts must be intensified in developing its human capital.